"Boots on the ground" state-building: Using Action Research to improve local governance in Afghanistan. Issue 3 (September 2021) - Ledet, Richard; Turner, Pete
This paper explains how the authors applied Action Research during Operation Enduring Freedom in the course of U.S. Department of Defense operations intended to improve local governance in Afghanistan. Serving as civilian field researchers in 2011–2012, we were tasked, in part, with observing how informal custom and authority interacted with the functioning of local government. Assisted greatly by Action Research's participatory nature, we were able to systematically develop a crucial relationship with an influential government official in a rural area. The partnership that resulted ultimately led to the implementation of planning procedures that were well suited to meet the needs of the district and more transparent to the Government of the Islamic Republic of Afghanistan and entities working with the U.S. Department of Defense. We argue that adopting and training for Action Research would increase the probability of success for current and future "non-lethal" U.S. Department of Defense activities.